Look who’s talking: deregulated signaling in colorectal cancer - Abba, Mohammed L.; Maier-Laufs, Stephanie; Benner, Axel; Allgayer, Heike (Cancer genomics & proteomics, 2012)
Background: The phenotypic expression of any given heterogeneous tissue type is the composite of interactions between individual cell types governed principally by inherent, cell-specific molecular mechanisms. Materials and Methods: Using a combination of laser-capture microdissection, oligonucleotide microarrays, bioinformatic and statistical tools, we analyzed colorectal cancer tissues in order to spot the significant pathways that were differentially deregulated between the epithelial and stromal compartments and compared these alongside the ones of whole tissue dissection. Results: The stromal pathway profiles were very similar to the ones of whole tissue, in contrast to the epithelial input, with stroma emerging as the major determinant of the cancer phenotype. Differentially expressed genes in the epithelial compartment correlated significantly with the carbohydrate antigen 19-9 tumor marker. Conclusion: The accurate interpretation of data arising from the analysis of heterogeneous tissue structures lends itself to inherent biases of its constitutive components with each component presenting explorable analytical advantages.